Traditional Authority and Security in Contemporary Nigeria - Ehrhardt, David; Oladimeji Alao, David; Umar, M. Sani (Routledge Studies in Peace, Conflict and Security in Africa, 2024)
Exploring the contentious landscape of Nigeria's escalating violence, this book describes the changing roles of traditional authorities in combatting contemporary security challenges. Set against a backdrop of widespread security threats - including insurgency, land disputes, communal violence, regional independence movements, and widespread criminal activities - perhaps more than ever before, Nigeria's conventional security infrastructure seems ill-equipped for the job. This book offers a fresh, empirical analysis of the roles of traditional authorities - including kings, Ezes, Obas, and Emirs - who are often hailed as potent alternatives to the state in security governance. It complicates the assumption that these traditional leaders, by virtue of their customary legitimacy and popular roots, are singularly effective in preventing and managing violence. Instead, in exploring their creative adaptation to governance roles after a dramatic postcolonial downturn, this book argues that traditional leaders can augment, but not substitute, the state in addressing insecurity. This book's in-depth analysis will be of interest to researchers and policy makers across African and security studies, political science, anthropology, and development. David Ehrhardt is an Associate Professor of International Development at Leiden University, The Netherlands. His main research interests are African governance and educational innovation. David has published extensively on Nigeria and co-leads the Learning Mindset project that promotes autonomous learning in higher education. David Oladimeji Alao is a Professor in the Department of Political Science and Public Administration, and Chief of Staff to the President/Vice Chancellor, Babcock University, Ogun State, Nigeria. Professor Alao has authored several articles and 3 edited books. M. Sani Umar is a Professor in the Department of History and Diplomatic Studies, University of Abuja, Nigeria. His research centres on religious vio- lence and peace building, with a focus on understanding the roots of religious conflict and the dynamics of religious pluralism.